ANALISIS DAYA SAING EKSPOR KELAPA INDONESIA DI PASAR INTERNASIONAL (Studi Pada Industri kopra Jawa Timur) - Andika Yoga Baskara; Supriono Supriono (Jurnal Administrasi Bisnis, 2018)
The purpose of this research is to know the competitiveness of Indonesian coconut exports in international market of study in copra industry of East Java. the analysis used is RCA analysis, and SWOT with qualitative approach. the result of this research is Kopra indonesia have competitiveness although competitiveness still brought Sri Langka in certain year. and for East Java has competitiveness although it does not have copra but East Java takes copra from other islands for export through port in East Java. for East Java's strength is the coconut plantations that exist in almost every province, have international ports, the weakness of many brokers, always lack of copra for export, the average of land ownership is limited and the location is far apart and the farmers prefer to sell only coconut. the threat of availability of raw materials, many land conversion functions, and the decreasing interest of farmers in processing copra. Keywords:Coconut, Copra, Competitiveness, Competitive Advantage, SWOTTO ABSTRAK Tujuan Ddari penelitianI,ini adalahUuntukrr mengetahui daya saing ekspor kelapa Indonesia di pasar internasional studi di industri kopra Jawa Timur. analisis yang di gunakan adalah analisis RCA, dan SWOT dengan pendekatan kualitatif. hasil penelitian ini adalah Kopra indonesia memiliki daya saing walaupun daya saingnya masih dibawa Sri Langka pada tahun tertentu. dan untuk Jawa Timur memiliki daya saing walaupun tidak memiliki kopra akan tetapi Jawa Timur mengambil kopra dari lain pulau untuk di ekspor lewat pelabuhan yang ada di Jawa Timur. untuk kekuatan Jawa Timur adalah perkebunan kelapa yang hampir ada di setiap provinsi, memiliki pelabuhan internasional,kelemahannya banyak broker, selalu kekurangan kopra untuk diekspor, rata rata kepemilikan lahan terbatas dan lokasinya berjauhan dan petani lebih memilih menjual kelapa saja. ancamannya ketersediaan bahan baku, banyak alih fungsi lahan, dan mulai berkurangnya minat petani dalam mengolah kopra Kata Kunci:Kelapa, Kopra, Daya Saing, Keunggulan Komparatif, SWOT